A NEW SPECIES OF FREZIERA (PENTAPHYLACACEAE) FROM ECUADOR, WITH LARGE LEAVES AND FLOWERS - Santamaría-Aguilar, D.; Neill, D. A.; Lagomarsino, L. P. (Edinburgh Journal of Botany, 2016)
Freziera grandiflora (Pentaphylacaceae), a new species from western Ecuador with relatively large leaves, flowers and fruits, is described and illustrated. Its distribution, phenology, habitat and relationship to allied species are discussed. Its conservation status is tentatively considered Vulnerable.
Keywords: Cloud forest; Ericales; Freziera; Pentaphylacaceae; Reserva Río Guajalito; Theaceae